Design, synthesis and glycosidase inhibition studies of novel triazole fused iminocyclitol-δ-lactams. Issue 5 (11th January 2019) - Santhanam, Venkatesan; Pant, Pradeep; Jayaram, B.; Ramesh, Namakkal G.
Abstract : Synthesis of novel triazole fused iminocyclitol-δ-lactams, from tri- O -benzyl-d -glucal, involving intermolecular [3 + 2]cycloaddition and intramolecular lactamisation reactions as key steps is described. Abstract : Synthesis of novel triazole fused iminocyclitol-δ-lactams is described. The synthetic sequence involves the intermolecular [3 + 2] cycloaddition reaction of five-membered iminocyclitol derived azides with diethylacetylene dicarboxylate followed by intramolecular lactamisation, decarboxylation/reduction and final deprotection. Compound3 is found to be a selective inhibitor of α-glucosidase from baker's yeast while two other compounds (2 and4 ) that possess an additional hydroxymethyl group in the triazole ring are selective against β-galactosidase from E. coli . Docking studies suggest the significance of the lactam carbonyl group for effective binding of these inhibitors with the active sites through hydrogen bonding.